1982
DOI: 10.1161/01.atv.2.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in rabbits fed a low cholesterol diet for five years.

Abstract: Rabbits were fed a low cholesterol atherogenic diet for up to 5 years. Arterial lesions during the first 12 months consisted of smooth muscle cell and lipid accumulation in the intima, with smaller amounts of elastin and collagen. By 24 months, considerable degeneration and necrosis of smooth muscle foam cells had occurred, lipid had decreased in relative proportion, and collagen was predominant. These trends continued during the final 3 years. By 48 months most plaques were calcified and a few had hemorrhage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 17 publications
0
21
0
2
Order By: Relevance
“…With low cholesterol diets, the atherogenesis is milder and slower in development, and smooth muscle cell proliferation is more prominent. 17 The cholesterol/phospholipid ratio was elevated in diabetic rabbits in this experiment, but the ratio was lower in diabetic rabbits fed much larger amounts of cholesterol. 4 Higher cholesterol/phospholipid ratios are usually associated with more extensive atherosclerosis.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…With low cholesterol diets, the atherogenesis is milder and slower in development, and smooth muscle cell proliferation is more prominent. 17 The cholesterol/phospholipid ratio was elevated in diabetic rabbits in this experiment, but the ratio was lower in diabetic rabbits fed much larger amounts of cholesterol. 4 Higher cholesterol/phospholipid ratios are usually associated with more extensive atherosclerosis.…”
Section: Discussionmentioning
confidence: 48%
“…In a study using the same diet as this experiment, 17 only three myocardial infarcts were found in about 70 normal rabbits fed the diet for as long as 5 years. Epidemiologic studies have indicated that ischemic myocardial disease and myocardial infarction are two to three times more frequent in diabetic than in nondiabetic people and that primary mortality is two to three times higher in diabetic patients.…”
Section: Discussionmentioning
confidence: 67%
“…[17][18][19][20] This is also supported by data in mice, where genetic ablation of hepatic MTTP expression in LDL receptor-deficient mice (LDLr −/− ) reduced plasma very low-density lipoprotein (VLDL) and LDL and led to more stable, less inflamed plaques. 21 More recent studies where aortic segments from atherosclerotic donor mice with high plasma VLDL/LDL levels were transplanted into healthy recipient mice with low plasma VLDL/LDL levels suggest that atherosclerotic plaques are highly dynamic.…”
Section: In This Issue See P 905mentioning
confidence: 63%
“…Most studies in animal models have relied on gross morphologic or histologic comparisons with human lesions. Multiple techniques have been used to produce atherosclerotic lesions in a variety of animal species, with cholesterol feeding 10 " 13 or mechanical trauma to the intima of the artery 14 " 18 being the most widely used. On the basis of studies using these lesions, numerous conclusions about the natural history, cellular biology, and biochemistry of the atherosclerotic plaque have been drawn.…”
Section: Discussionmentioning
confidence: 99%
“…These include lack or paucity of ulceration, hemorrhage, or fibrous cap in the lesion; location of the lesion in the proximal parts of the aorta rather than the distal; predominant involvement of intramyocardial branches of the coronary arteries rather than of epicardial arteries; and the widespread deposition of cholesterol in such organs as the liver, spleen, skin, and eye. 13 '…”
Section: Discussionmentioning
confidence: 99%